2003
DOI: 10.1002/14651858.cd004058
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency denervation for neck and back pain

Abstract: The selected trials provide limited evidence that radiofrequency denervation offers short-term relief for chronic neck pain of zygapophyseal joint origin and for chronic cervicobrachial pain; conflicting evidence on the short-term effect of radiofrequency lesioning on pain and disability in chronic low-back pain of zygapophyseal joint origin; and limited evidence that intradiscal radiofrequency thermocoagulation is not effective for chronic discogenic low-back pain. There is a need for further high-quality RCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…For patients with cervicobrachial pain, radiofrequency denervation might provide short-term pain relief. 119 Other commonly used treatment options for neck pain are a collar, NSAIDs, psychotropic medication, electrotherapy, and transcutaneous electrical nerve stimulation. Whether these interventions are eff ective or not is still unclear.…”
Section: Percutaneous Tenotomy or Formal Open Releasementioning
confidence: 99%
“…For patients with cervicobrachial pain, radiofrequency denervation might provide short-term pain relief. 119 Other commonly used treatment options for neck pain are a collar, NSAIDs, psychotropic medication, electrotherapy, and transcutaneous electrical nerve stimulation. Whether these interventions are eff ective or not is still unclear.…”
Section: Percutaneous Tenotomy or Formal Open Releasementioning
confidence: 99%
“…Compared with operative options, it is considered a relatively safe and less complicated technique; its recognized adverse effects only being transient radiculopathy and a case report of skin burn due to poor earthing (7,(9)(10)(11). Extensive literature exists on this technique with a number of randomized controlled studies suggesting its efficacy against placebo (10,(12)(13)(14)(15)(16), while other studies have questioned its efficacy (8,9,11,17,18). Evaluation of evidence regarding this technique has often drawn criticism for the lack of volume of high-quality studies for comparison because existing randomized controlled trials on this procedure have different diagnostic criteria and surgical techniques between them (17).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive literature exists on this technique with a number of randomized controlled studies suggesting its efficacy against placebo (10,(12)(13)(14)(15)(16), while other studies have questioned its efficacy (8,9,11,17,18). Evaluation of evidence regarding this technique has often drawn criticism for the lack of volume of high-quality studies for comparison because existing randomized controlled trials on this procedure have different diagnostic criteria and surgical techniques between them (17). Despite the debate regarding evidence of effectiveness of the procedure, lumbar percutaneous radiofrequency facet joint denervation [RFJD] appears to have gained popularity in recent times.…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane systematic review concluded that there is "limited evidence that RF denervation offers short-term relief for chronic neck pain of zygapophyseal joint origin and for chronic cervicobrachial pain" and "conflicting evidence on the short-term effect of RF lesioning on pain and disability in chronic low-back pain of zygapophyseal joint origin." 8 Chou et al 9 in an evidence-based American Pain Society Clinical Practice Guideline found "insufficient evidence to adequately evaluate benefits of" therapeutic medial branch blocks and RF denervation for low back pain.…”
Section: Risks and Benefitsmentioning
confidence: 99%